Biological Impact of Unilateral Oophorectomy: Does the Number of Ovaries Really Matter? - Gasparri, Maria Luisa; Ruscito, Ilary; Braicu, Elena Ioana; Sehouli, Jalid; Tramontano, Luca; Costanzi, Flavia; De Marco, Maria Paola; Mueller, Michael D.; Papadia, Andrea; Caserta, Donatella; Bellati, Filippo (Geburtshilfe und Frauenheilkunde, 2020)
Although unilateral oophorectomies are performed more often than bilateral ones in women of reproductive age, their clinical consequences have been less intensively investigated. Experimental models in animals have shown that compensatory mechanisms occur after a unilateral oophorectomy (UO). This review aims to summarize the available evidence on the biological effects of unilateral oophorectomy on women. Evaluated outcomes include age at onset of menopause, risk of cardiovascular and neurological disease, risk of mortality and fertility outcome after spontaneous conception or in vitro fertilization (IVF). Results were compared with findings reported after bilateral oophorectomy and/or ovarian excision and/or women with intact ovaries. An electronic database search was performed using PubMed and Scopus, followed by a manual search to identify controlled studies that compared women after UO with women with two intact ovaries. In particular, a systematic review of fertility outcomes after IVF was performed, and the data were summarized in a table. Women who underwent UO had a similar age at menopause and similar clinical pregnancy rate compared to women with two ovaries. However, decreased ovarian reserve affecting the quantity but not the quality of the ovarian pool after IVF was observed in the UO group. Furthermore, an increased risk of neurological disease and even an increased risk of mortality was observed in women with single ovary. These data need to be confirmed by further studies, and a plausible mechanism of action must be identified. At present, patients who undergo UO can be reassured with regard to their reproductive potential and their age at onset of menopause.
Keywords: unilateral oophorectomy; fertility; IVF; pregnancy rate; conservative surgery; ovarian cystectomy